(untitled) - Zenaida F Toquero Rebecca C Torres (Los Bamos, Languna, Philippines, 1998)
The book is a synthesis of research results from an International Development Research Centre-funded project on "Women in postproduction systems". Special emphasis is gives to the stutus and role of women in postproduction activities
Keywords: agriculture - economic aspects